Construction of roof beam structure / Daeng Arqeelia Zaisarah Mohamed Seth - Mohamed Seth, Daeng Arqeelia Zaisarah (2021)
Roof beam is a horizontal structural element that is built after the installation of column of the building. Roof beam structure is important as the final structure after column as it is used to bear the loads from roof trusses and roof covering. Therefore, this report will discuss about the installation of roof beam structure. This report was conducted at a construction site of a bungalow house located in a neighbourhood named Taman Setia Hati located in Sungai Landak, Seremban District, Negeri Sembilan. The objective of this report is to determine the process of roof beam structure is built on site. It will focus on the stages on how the process of the roof beam is done and carried out. This report will also look at the defects that are found on the structural elements. Last but not least, it will also explain the materials and tools that are used to solve the problems of the defects. From erecting the scaffolding, installing the formwork, pouring the concrete, compacting and curing the final result of the roof beam after the hardening process are done on site. To finalized, the installation of roof beam on the building project plays an important role as it holds the loads from installing the roof trusses and roof covering which protects the residence inside the house from weather and safe from any harms in the future.